Hymenoptera do membro Crato (aptiano) da formação Santana, Bacia do Araripe - Carvalho, Gabriela Karine Rocha de (2017)
The present work describes new specimens of hymenoptera from limestone of the Crato Member (Aptian) of the Santana Formation, Araripe Basin, which appear in the city of Nova Olinda, southern Ceará State. It also presents the current state of knowledge of the fossils of this order, as well as the taphonomy, ecology and paleogeography of the families found in the Crato Member during the Early Cretaceous. The study of 47 specimens of Hymenoptera from the collections revealed the occurrence of eleven families and 21 species. Among these, a specimen of Siricidae, with genus and new species, a new genus and two new species of Sapygidae, and the presence of two genera described, one of Ephialtitidae, with a new species, and another for Sphecidae and three new species were described. In the Araripe Basin, the number of representatives of the suborder Symphyta is still low, with only the families Siricidae and Sepulcidae known. The Apocrita are more diversified, with the Parasitica assembling forms of Ichneumonoidea, Ephialtitidae, Proctotrupidae, Mesoserphidae, Pteromalidae and Evaniidae. The Aculeata with species of Sphecidae (most abundant and diverse), Sapygidae, Rhopalosomatidae, Scoliidae, Tiphiidae, Vespidae and Formicidae, the latter being questioned. The hymenoptera of Crato Member are preserved by mineral substitution, articulated, with open wings and extended legs, showing more number of female specimens than males, without known larvae. It is a fauna not very distinct from the main known eocretácea hymenopterofaunas (Spain, Mongolia, China, Russia, England and Australia), sharing some genera.